2014
DOI: 10.2340/00015555-1738
|View full text |Cite
|
Sign up to set email alerts
|

Mild Eczema Affects Self-perceived Health among Pre-adolescent Girls

Abstract: The aim was to assess the impact of eczema on health-related quality of life in the population-based birth cohort BAMSE with 2,756 pre-adolescent children. All answered the following questions on self-perceived health; "How are you feeling?", "How healthy do you consider yourself to be?" and "How happy are you with your life right now?". Children with ongoing eczema answered the "Children's Dermatology Life Quality Index (CDLQI)" questionnaire. In total, 350 (12.7%) of the children had eczema. Girls with eczem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
16
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 27 publications
3
16
0
Order By: Relevance
“…We demonstrated a convincing gender difference in our population of patients ≥ 17 years with ongoing eczema regardless of the natural history. Similar to our results, Ballardini et al (18) found pre-adolescent girls with mild eczema to have greater impairment of selfperceived health compared to boys. Our finding may well reflect that adolescent girls and young women are more concerned about appearance than males of the same age.…”
Section: Discussionsupporting
confidence: 92%
“…We demonstrated a convincing gender difference in our population of patients ≥ 17 years with ongoing eczema regardless of the natural history. Similar to our results, Ballardini et al (18) found pre-adolescent girls with mild eczema to have greater impairment of selfperceived health compared to boys. Our finding may well reflect that adolescent girls and young women are more concerned about appearance than males of the same age.…”
Section: Discussionsupporting
confidence: 92%
“…11 Since eczema is a visible disease it may have a strong impact on HRQoL, particularly among adolescent girls who often are sensitive about their appearance. 38 These results support the importance of identifying and treating not only asthma but also co-morbid conditions such as eczema.…”
Section: Discussionsupporting
confidence: 61%
“…In line with our result, population‐based studies with adolescents indicate that both eczema, and reported allergic diseases (ie, asthma/wheezing, eczema/rash, rhino‐conjunctivitis) have a negative impact on HRQoL . Since eczema is a visible disease it may have a strong impact on HRQoL, particularly among adolescent girls who often are sensitive about their appearance . These results support the importance of identifying and treating not only asthma but also co‐morbid conditions such as eczema.…”
Section: Discussionmentioning
confidence: 52%
“…As the questions in the KIDSCEEN‐10 HRQoL questionnaire only take the previous week into account, teenagers who only experienced rhinitis during the pollen season would be expected to report normal HRQoL outside the pollen season. Having eczema was related to poor HRQoL in accordance with other studies . As eczema is a visible disease, it may affect an individual's social life and have a strong impact on HRQoL, particularly among teenagers who often are sensitive about their appearance.…”
Section: Discussionsupporting
confidence: 89%